Marketing Analysis of Local Food Saparua Brown Sugar in Ambon City - Sapulette, Alvian -; Huesepuny, Harold -; Nunumete, Laura - (Politeknik Negeri Semarang, 2025)
Indonesia stretches from the western tip to the eastern tip, from Sabang to Merauke, and has various potential resources that can be economically developed by the business world and society in the form of manufacturing businesses, home industries, and economic empowerment as an effort to drive the wheels of the nation's economy. The forms of community empowerment efforts vary according to potential. One of the many efforts is the production of brown sugar. The brown sugar business in Saparua, Tuhaha Village, Saparua Timur District, Central Maluku Regency, Maluku Province is mostly carried out by brown sugar farmers as a home industry with limited equipment, simple processing management and marketing systems. The purpose of this study is to determine how the design of the strategy and marketing tactics of Saparua palm sugar products in Tuhaha Village, Central Maluku Regency by identifying internal and external conditions. This study is different from previous studies where in this study an STP strategy analysis (segmentation, targeting and positioning) was carried out by looking at the existing conditions of Saparua palm sugar marketing to formulate the direction of the strategy policy and marketing tactics of Saparua brown sugar